THE PHYSICAL PROPERTIES OF CEMENTITIOUS COMPOSITES FOR APPLICATIONS IN A HIGH-TEMPERATURE ENERGY STORAGE DEVICE - Stanislav Šťastník; Lenka Bodnárová (Acta Polytechnica CTU Proceedings)
The article was focused on experimental verification of the identification of thermal characteristics of high-performance cementitious composites at elevated temperatures. The purpose of the research was to verify the properties, and consequently the suitability of these special cement composites for the production of a heat storage device for the long-term accumulation of thermal energy. The theoretical prerequisites for the identification of thermal characteristics and the practical procedure of experimental verification of the characteristics were presented. A modified procedure for the determination of temperature conductivity α by the hot wire method was suggested. Subsequently, the experimental verification and the results of the measured thermal characteristics were listed – and the temperature conductivity α, the thermal conductivity λ[w/m·K], the volumetric heat capacity and the specific heat capacity c[J/kg·K] by the modified method were determined.